Implementasi Nilai-Nilai Kepedilian Sosial Dalam Al-Quran - Mohammad Alfan Ni’am; Nova Fitriya; Ana Rahmawati (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
One of the important values ​​taught in the Qur'an, especially in Surah al-Ma'un, is social concern. Surah al-Ma'un emphasizes the importance of providing care to the weak, such as orphans and the poor, and invites Muslims to not only focus on their vertical relationship with Allah, but also make it an important part of their worship and religious practice. other. The Qur'an defines social concern as true faith. In Surah al-Ma'un, Allah warns that people who ignore their obligations to society and do not care about their neighbors are considered religious liars. This shows that faith can be measured by social concern. Therefore, having an attitude of empathy and solidarity with other people is very important in the life of a Muslim. The Qur'an says social concern is the true faith. In Surah al-Ma'un, Allah warns that those who neglect their obligations to society and do not care about their fellow men are considered religious liars. This shows that social concern can measure faith. As a result, having an attitude of empathy and solidarity with others is very important in the life of a Muslim. Al-Azhar's interpretation, according to Buya Hamka, covers various aspects of social care, such as looking after and caring for orphans and the poor. A true understanding of religion will encourage people to be more sensitive to the needs of other people, said Buya Hamka. Therefore, so that future generations have high social awareness, education about social awareness must be part of the Islamic education program. Overall, the values ​​of social care found in the Qur'an invite people to do good and build a just and prosperous society. By understanding and applying these teachings, Muslims are expected to be able to create an environment where people support and care for each other, which results in harmony in social life.